Теоретико-правова характеристика адміністративно-правового статусу Національної поліції України як суб’єкта здійснення превентивної діяльності - Шевченко, В. М.; Shevchenko, V. M. (Науковий вісник публічного та приватного права. - 2023. - Вип. 6. - С. 171-176, 2023)
Статтю присвячено теоретико-правовому дослідженню категорії «адміністративно-правовий статус Національної поліції України як суб’єкта здійснення превентивної діяльності». Зроблено висновок, що адміністративно-правовий статус Національної поліції України як суб’єкта здійснення превентивної діяльності є складною юридичною категорією, яка: 1) має багатоелементну блокову структуру, визначені адміністративно-правовими нормами функціонально-цільові, структурно-організаційні, компетенційні, обмежувально-забезпечуючі елементи якої цілісно та системно формують його зміст, виступаючи значимими та індивідуалізуючими властивостями та характеристиками Національної поліції України як суб’єкта здійснення превентивної діяльності; 2) визначає місце, роль та функціональне призначення Національної поліції як суб’єкта здійснення превентивної діяльності, що вирізняє її з-поміж інших центральних органів виконавчої влади та реалізується шляхом виконання визначених завдань в межах її компетенції за конкретними напрямами діяльності (функціями) задля досягнення мети функціонування у сферах забезпечення публічної безпеки і порядку; охорони прав і свобод людини, а також інтересів суспільства і держави; протидії злочинності; 3) відображає характер правових зв’язків та особливості взаємодії Національної поліції як суб’єкта здійснення превентивної діяльності з органами правопорядку, іншими органами державної влади, населенням.

The article is devoted to the theoretical and legal study of the category «administrative and legal status of the National Police of Ukraine as a subject of preventive activities». It was concluded that the administrative-legal status of the National Police of Ukraine as a subject of preventive activity is a complex legal category, which: 1) has a multi-element block structure, functional-purpose, structural-organizational, competent, restrictive-providing, defined by administrative-legal norms the elements of which integrally and systematically form its content, acting as significant and individualizing properties and characteristics of the National Police of Ukraine as a subject of preventive activity; 2) determines the place, role and functional purpose of the National Police as a subject of preventive activity, which distinguishes it from other central bodies of the executive power and is implemented by performing specified tasks within the limits of its competence in specific areas of activity (functions) in order to achieve the goal functioning in the areas of ensuring public safety and order; protection of human rights and freedoms, as well as the interests of society and the state; combating crime; 3) reflects the nature of legal relationships and the peculiarities of the interaction of the National Police as a subject of preventive activities with law enforcement agencies, other state authorities, and the population. It was determined that the structural-organizational block of elements of the administrative-legal status of the National Police of Ukraine as a subject of preventive activity is determined by functional-target (goal, tasks, functions) elements, which, together with the competence block, characterize the limits and procedure of preventive activity by the National Police, and legal responsibility, as a limiting and ensuring element, guarantees proper implementation of defined tasks and achievement of the goal of functioning of the National Police, ensuring the legality of its activities.

Статья посвящена теоретико-правовому исследованию категории «административно-правовой статус Национальной полиции Украины как субъекта осуществления превентивной деятельности». Заключено, что административно-правовой статус Национальной полиции Украины как субъекта осуществления превентивной деятельности является сложной юридической категорией, которая: 1) имеет многоэлементную блочную структуру, определенные административно-правовыми нормами функционально-целевые, структурно-организационные, компетенционные, ограничительно-обеспечивающие элементы которой целостно и системно формируют его содержание, выступая значимыми и индивидуализирующими свойствами и характеристиками Национальной полиции как субъекта осуществления превентивной деятельности; 2) определяет место, роль и функциональное назначение Национальной полиции как субъекта осуществления превентивной деятельности, что отличает ее от других центральных органов исполнительной власти и реализуется путем выполнения определенных задач в пределах ее компетенции по конкретным направлениям деятельности (функциям) для достижения цели функционирование в сфере обеспечения публичной безопасности и порядка; охраны прав и свобод человека, а также интересы общества и государства; противодействия преступности; 3) отражает характер правовых связей и особенности взаимодействия Национальной полиции как субъекта осуществления превентивной деятельности с органами правопорядка, другими органами государственной власти, населением.
Theoretical and legal characteristics of the administrative and legal status of the National Police of Ukraine as a subject of preventive activities
Keywords: правовий статус; адміністративно-правовий статус; Національна поліція; превентивна діяльність; превентивна функція; превенція; поліцейська діяльність; legal status; administrative-legal status; National Police; preventive activity; preventive function; prevention; police activity; правовой статус; административно-правовой статус; Национальная полиция; превентивная деятельность; превентивная функция; превенция; полицейская деятельность